PELAKSANAAN TUGAS SUPERVISOR PADA DEPARTEMEN FRONT OFFICE DI HOTEL IBIS PEKANBARU PROVINSI RIAU - Masnur, Munazir Prio; Achnes, Syofia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research purposed to get know how the supervisor implementation tasks in Front Office Department in Ibis Hotel Pekanbaru Riau Province and the faced constraints in the implementation tasks that supervisor did in front office department of Ibis Hotel.This research used qualitative desciptive method to analyze the problems. The sample in this research are 12 samples by using census sampling. And then the techniques to collected data in this research are using observation, questionnaire and interview. And it was using likert scale to know the length of intervals.Based on the research, respond from the staff about the implementation task of the supervisor in front office department in Ibis Hotel are planning, coordinating, briefing, controlling and evaluating. Which in briefing phaseall staffs of front office thought that the tasks implementation that suoervisor did in front office department of Ibis Hotel Pekanbaru are still less well.Key words : Tasks Implementation, Supervisor, Front Office Department, Ibis Hotel